Novel N-propylphthalimide- and 4-vinylbenzyl-substituted benzimidazole salts: Synthesis, characterization, and determination of their metal chelating effects and inhibition profiles against acetylcholinesterase and carbonic anhydrase enzymes - Yakup, Sari; Aydin, Aktas; Taslimi, Parham; Yetkin, Gok; Gülçin, İlhami; Taslimi, Parham (Wiley, 2018)
The novel N-propylphthalimide-substituted and 4-vinylbenzyl-substituted N-heterocyclic carbene (NHC) precursors were synthesized by N-substituted benzimidazolium with aryl halides. The novel N-propylphthalimide-substituted and 4-vinylbenzyl-substituted NHC precursors have been characterized by using H-1 NMR, C-13 NMR, FTIR spectroscopy, and elemental analysis techniques. They were tested for the inhibition of AChE and hCA enzymes and demonstrated efficient inhibition profiles with K-i values in the range of 351.0-1269.9 nM against hCA I, 346.6-1193.1 nM against hCA II, and 19.0-76.3 nM against AChE. On the other hand, acetazolamide, a clinically used molecule, utilized as CA inhibitor, obtained a K-i value of 1246.7 nM against hCA I and 1407.6 nM against hCA II. Additionally, tacrine inhibited AChE and obtained a K-i value of 174.6 nM.
Keywords: N-heterocyclic carbene precursors; Acetylcholinesterase; Benzimidazole; Carbonic anhydrase; Metal chelating